Agro-based mobile apps Adoption among Bangladeshi farmers at the ‘Hamlet’ of Bangladesh – A Case Study of Chandpura Village of Barisal - Afruza Akter,; Kim, Hua Tan (Penerbit Universiti Kebangsaan Malaysia, 2023)
Farmers in Bangladesh are gradually adopting and using ICT-based agricultural applications. This study attempted to identify the factors influencing the use of agro-based mobile applications by farmers in Chandpura village of Barisal district. The study examined farmers' access to ICT in terms of smartphone ownership, internet access, their ICT use behaviour for agriculture, and their knowledge and use of agro-based mobile applications. The research was conducted following the principles of qualitative methods in case studies. For data collection and analysis, in-depth interviews, semi-structured questionnaires, and narrative data analysis were utilised. The results showed that farmers were primarily influenced by personal factors such as need, age, education, and satisfaction. The youth were more receptive to innovations because they were more educated and adaptable. In addition, technological factors, such as access to a device and the internet, digital knowledge, ease of use, and a support network, played a significant role in this regard. While the study helped us understand the significance of ICT technology for the continued development of the agricultural sector, market and weather information were neglected in agro apps for small villages where disease, market, and weather information took precedence. Before implementing any technology, it is crucial to conduct research on the population and their specific needs. The implication is that the study helped us comprehend the significance of ICT technology for the advancement of the agriculture sector, even in small villages, and how implementing an ICT-based "agricultural advisory service" supported and benefited farmers.